Tanah, Otoritas Politik, dan Stabilitas Ekonomi Kerajaan Mataram Islam (1613-1645 M) - Zaid Munawar (Universitas Negeri Padang, 2021)
This article examines issues of land, political authority, and economic stability of the Islamic Mataram Kingdom during the reign of Sultan Agung (1613-1645 AD). This study uses the historical method by carrying out steps such as topic selection, heuristics, verification, interpretation and historiography. This research shows that Sultan Agung as a king has full authority over land management in the entire territory of the Islamic Mataram Kingdom. So that the land can be managed properly, the Sultan Agung divides the land based on concentric circles of the territory, both in the territory of the Negara Agung, Mancanegara, and Pasisiran in order to build a community under the auspices of his government. There are three types of land that are known in this division, namely narawita land (land in the core area of ​​the kingdom which is used as agricultural land and plantations to produce rice, flowers, grass, oil, etc. for palace purposes), lungguh/apanage land (land in the territory of the Negara Agung, Mancanegara, and Pasisiran distributed to the nobles and royal officials as land salaries for their role in the continuity of the administration, and perdikan land (village land in which there are royal sacred buildings, such as places of worship, tombs, and the like, which are exempt from taxation as given to religious leaders (ulama and penghulu). These lands are mainly managed for agriculture as the most important economic source for the kingdom. The maximization of land management is able to have a positive impact on economic stability and governance in the Islamic Mataram Kingdom. Keywords: Land, Political Authority, Economic Stability, Islamic Mataram Kingdom Artikel ini bertujuan mengkaji tentang persoalan tanah, otoritas politik, dan stabilitas ekonomi Kerajaan Mataram Islam pada masa kekuasaaan Sultan Agung (1613-1645 M). Penelitian ini menggunakan metode sejarah dengan melakukan langkah-langkah seperti pemilihan topik, heuristik, verifikasi, interpretasi dan historiografi. Hasil penelitian menunjukkan bahwa Sultan Agung sebagai seorang raja memiliki otoritas penuh terhadap pengelolaan tanah di seluruh wilayah kekuasaan Kerajaan Mataram Islam. Agar tanah tersebut dapat dikelola dengan baik, maka Sultan Agung membagi tanah berdasarkan lingkaran konsentris wilayah kekuasaan, baik di wilayah Negara Agung, Mancanegara maupun Pasisiran demi membangun masyarakat yang berada dalam naungan pemerintahannya. Ada tiga jenis tanah yang dikenal dalam pembagian tersebut, yaitu tanah narawita (tanah di wilayah inti kerajaan yang digunakan sebagai tanah pertanian dan perkebunan agar menghasilkan padi, bunga, rumput, minyak, dan lain-lain untuk keperluan istana), tanah lungguh/apanage (tanah di wilayah Negara Agung, Mancanegara dan Pasisiran yang didistribusikan kepada para bangsawan dan pejabat tinggi kerajaan sebagai tanah gaji atas perannya terhadap kelangsungan jalannya pemerintahan), dan tanah perdikan (tanah desa yang di dalamnya terdapat bangunan suci kerajaan, seperti tempat ibadah, makam, dan semacamnya, yang dibebaskan dari pungutan pajak sebagaimana diberikan kepada para tokoh agama (ulama dan penghulu). Tanah-tanah tersebut dikelola terutama untuk pertanian sebagai sumber ekonomi terpenting bagi kerajaan. Maksimalisasi pengelolaan tanah tersebut mampu memberikan dampak positif bagi stabilitas ekonomi dan pemerintahan di Kerajaan Mataram Islam. Kata Kunci: Tanah, Otoritas Politik, Stabilitas Ekonomi, Kerajaan Mataram Islam